Formulation and Antioxidant Activity Test of Michelia champaca Linn. Flower Methanol Extract Gel Using DPPH (2,2-Diphenyl-1-Picrylhydrazyl) Method - Mendra, Ni Nyoman Yudianti; Puspayanti, Ni Made; Antari, Ni Putu Udayana; Suradnyana, I Gede Made; Rahadi , I Wayan Surya (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2023)
Michelia champaca, a tropical evergreen flower utilized for religious rituals in Bali, exhibits notable level of flavonoid with potent antioxidant properties. This study aims to investigate the antioxidant activity of gel formulation using methanol extract of Michelia champaca flowers. The gel formulations were prepared using varying concentration of the extract (5%, 7,5%, and 10%), and underwent physical evaluations. Statistical analysis was performed using SPSS version 22 at a 95% confidence level. The results showed gel formulations exhibit desirable physical characteristics, indicated by the presence of homogenous yellow-brown gel with the fragrance of extract, a spreadability range of 4.83-6.90 cm, adhesion time of 2.293-2.616 seconds, and pH of 5. The dispersion test revealed no significant difference between all formulations. The antioxidant activity was determined using DPPH radical scavenging assay, with IC50 values indicating the efficacy of gel. The IC50 values for FI, FII, and FIII were 49,859 µg/ml, 23.774 µg/ml, and 6.626 µg/ml, respectively, compared to the IC50 value of vitamin C 4,861 µg/ml. These results indicate that the Michelia champaca methanol extract gel possesses potent antioxidant activity. Moreover, the higher concentration of the extract exhibited a smaller IC50 value, indicating increased efficacy in scavenging free radicals.